Faktor Perilaku Yang Berhubungan Dengan Kejadian Karies Gigi Pada Anak Usia 7 – 12 Tahun Di SDN Paku Alam Desa Paku Alam Kecamatan Sungai Tabuk Kabupaten Banjar Provinsi Kalimantan Selatan - sri nuryati (Politeknik Kementerian Kesehatan Banjarmasin, 2018)
Background : From Banjar district data showed 7.80 DF-T number, meaning that on average everyone in the Banjar district had almost 8 teeth with dental caries. Children of Elementary School age, i.e. 7-12 years, are of age who are susceptible to the occurrence of dental caries. Report on the screening of school-age children SD/MI conducted by the Sungai Tabuk 2 society health center (Puskesmas) in 2016 and 2017, the results of the screening on Paku Alam Elementary School’s students showed that during the last two years the number of students experiencing caries had increased. The percentage of students who experienced caries in 2016 was 79.2% and increased to 100% in 2017. Aim : This research wants to find out the behavioral factors related with the incidence of dental caries in children aged 7-12 years in the natural nails of Banjar Regency, South Kalimantan Province. Method : The study design was descriptive analytic that is cross sectional. The population and sample of the study were all children aged 7-12 years at the Paku Alam Elementary School Banjar distirct, South Kalimantan Province. The data will be analyzed analytically using Chi Square. Result : Descriptive results showed that most respondents experienced high dental caries (94.9%), had poor tooth brushing behavior (82.3%), poor cariogenic food consumption (62%), and no dental check-ups once every 6 month (98.7%). Analytically, there are no behavioral factors related to the incidence of dental caries. Conclusion : No behavioral factors that are significantly related with the incidence of dental caries in children. Keywords : Behavior, Children’s dental caries